Analysis of Cascading Effect on Different Tax Period Invoice Crediting Policy - Rusdiono, Leander Resadhatu; Rahayu, Ning (Green Publisher Indonesia, 2024)
Value Added Tax (VAT) is a development of Sales Tax that has a non-cumulative nature, so it avoids the occurrence of tax on tax or cascading effect. Regarding the provisions on input tax crediting as regulated in Article 9 paragraph (2) and paragraph (9) of the VAT Law, input tax credit can be made in the same Tax Period. In practice, there are often conditions that eventually cause Input Tax crediting to be carried out in different Tax Periods. In 2022, the Directorate General of Taxes (DGT) issued a policy on different tax period invoice credits (FP) which is regulated in Regulation of the Director General of Taxes Number PER-03/PJ/2022. This policy regulates the time limit for uploading, which previously did not exist. This upload time limit tends to have a cascading effect. This study aims to further analyze the cascading effect caused by the implementation of the different tax period invoice credit policy as regulated in PER-03/PJ/2022. This study uses a qualitative research method with data analysis techniques conducted through literature studies. The results of this study show that the different tax period invoice credit policy, especially that regulated in Article 18 PER-03/PJ/2022, tends to cause a cascading effect where there are input invoices that cannot be credited.